Envejecimiento y migración en Baja California - Elmyra Ybañez Zepeda (El Colegio de la Frontera Norte, 2007)
In the future, the population of 60 years old or older will increase in absolute and relative numbers at a very rapid pace in Mexico. Using data from Censo general de población y vivienda 2000, Encuesta sobre migración en la frontera norte de México and Consejo Nacional de Población (Conapo), the purpose of this article is twofold: first of all, to analyze the aging process in the municipalities of Tijuana and Mexicali, located in the state of Baja California, which has a very low proportion of the eldest; and second of all, to examine the role of migration in this process. Tijuana has a younger population which is aging slowly due to a very intense immigration of young workers and potential parents. Mexicali, on the other hand, has a high percentage of a native population that is aging unrelentingly, and it also has a lower flow of immigrants who are older, and includes a high concentration of persons who had previously resided in the United States.